Problems and Ways of Improving the Business Climate in the Regions - Uruzbaeva, Nazym Aminovna (Economy of Regions, 2016)
The existence of the specific conditions and development factors of small and medium-sized enterprises (SMEs) in the regions of Kazakhstan supposes the differentiated state policy in order to maintain a favorable business climate. The article presents the results of the research whose purpose was to determine the main issues and directions of the improvement of the business climate in the regions. This allows to intensify the activities of local authorities in support of SMEs considering the peculiarities of the territories' development. The subject matter of this research is the conditions and factors generating the business climate of the region. As a hypothesis, a direct connection between the prevailing regional business climate and the development of the quantitative indicators of active SMEs in the field was assumed. The study used the method of comparative analysis, sociological methods of focus groups, survey research, statistical methods and statistical methods of ranking and grouping. The article theoretically substantiates the correctness of the usage of «business climate» category as a scope of the study in the framework of the project of «Implementation of «Business Climate» as an Independent Rating», which makes possible the argumentation of the used methodology and concretization of the factors affecting the functioning of SMEs in the regions. This research has confirmed the direct correlation between the established business climate in the regions and quantitative indicators of the development of SMEs at the local level. Such factors as “financial resources” and “government support” have been determined as limiting the business development in a greater degree. In conclusion, a set of measures to improve the business climate in the region both at national and regional levels of government has been provided. In addition, it has been concluded that to generate a favorable business environment in the regions of Kazakhstan, it is necessary to make a smooth transition from a policy of “identification and punishment of unfair entrepreneurs” to a policy of “prevention and promotion of good business". The results of the research can be used in the work of the local executive authorities in order to improve the business climate in the regions of the country.